2019
DOI: 10.1186/s13046-019-1462-y
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated knockout of NSD1 suppresses the hepatocellular carcinoma development via the NSD1/H3/Wnt10b signaling pathway

Abstract: BackgroundThe NSD family of histone lysine methyltransferases have emerged as important biomarkers that participate in a variety of malignancies. Recent evidence has indicated that somatic dysregulation of the nuclear receptor binding SET domain-containing protein 1 (NSD1) is associated with the tumorigenesis in HCC, suggesting that NSD1 may serve as a prognostic target for this malignant tumor. However, its mechanism in human hepatocellular carcinoma (HCC), the major primary malignant tumor in the human liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…In liver cancer, NSD1 was highly expressed, and knockdown of NSD1 could inhibit the cell proliferation, migration and invasion, and inhibited the expression of WNT10B [24]. NSD1 could also affect the progression of HCC through WNT10B [25]. Therefore, we speculated that, in GC, NSD1 may also inhibit the progression of GC through this signaling pathway.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In liver cancer, NSD1 was highly expressed, and knockdown of NSD1 could inhibit the cell proliferation, migration and invasion, and inhibited the expression of WNT10B [24]. NSD1 could also affect the progression of HCC through WNT10B [25]. Therefore, we speculated that, in GC, NSD1 may also inhibit the progression of GC through this signaling pathway.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the important role of NSD1 in the progression and development of multiple types of tumors has been widely revealed [16]. For example, NSD1 suppressed HCC progression via the NSD1/WNT10B pathway [17]. NSD1 was also highly expressed in pancreatic ductal adenocarcinoma tissues and correlated with its prognosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…The HIF‐1α knockout in SMMC 7721 cells significantly inhibited cell invasiveness and migration and prolonged the survival of HCC‐bearing mice. 92 In another report, it was shown that a CRISPR/Cas9‐mediated NSD1 knockout suppressed HCC cell proliferation, migration and invasion via the Wnt/β‐catenin signalling pathway 93 (Figure 2B ).…”
Section: Gene Therapy In Hccmentioning
confidence: 92%
“…177 Similar modifications can be detected in the Wnt10b promoter region in HCC; these modifications activate the Wnt/β-catenin signaling pathway and reinforce cell proliferation, migration, and invasion. 178 Moreover, PRMT6-overexpressing GC cells also acquire invasiveness through direct transcriptional inhibition of PCDH7 by increasing H3R2me2as level. 179 Another study conducted by Li et al demonstrated that H3K27me3 and H3K9me2, mediated directly and indirectly by EZH2, are enriched in the miR-218-2 promoter, thus leading to downregulation of gene expression in PC.…”
Section: Invasion and Migrationmentioning
confidence: 99%